Events after Reporting Period and Misstatements in Quarterly Accounts - Saidin, Saidatunur Fauzi; Malek, Mazrah; Ibrahim, Daing Nasir; Kee, Phua Lian (International Journal of Economics and Financial Issues, 2016)
The occurrence of deviation between annual and cumulative quarterly accounts has been postulated as a signal of low reliability in quarterly accounts. This study examines whether the earnings deviation is more related to misstatements rather than the occurrence of events after reporting period. Data is based on Bursa Malaysia listed companies consisting of 731 observations for the period of between 2000 until 2012. Only a total of 14 percent had declared events after reporting period, while 95 percent have declared misstatements as reasons for earnings deviation. Results of the t-test show that the magnitude of earnings deviation related to misstatements is significantly higher than those related to events after reporting period. The results suggest that earnings deviation is more related to low quality of quarterly earnings, instead of mandatory accounting adjustments. Finding suggests the need for the company and regulators to take actions to enhance the quality of quarterly accounts. Keywords: events after reporting period, misstatements, quarterly accounts JEL Classifications: M41, M42, M48